State of Training for Surgery in Austere Environments - A Review of the Literature - Linn, Yun Le; Khoo, Nathanelle Xiaolian; Lie, Denny Tijauw Tjoen; Chan, Yew Weng; Chong, Tsung Wen; Tan, Hiang Khoon; Ho, Henry Sun Sien; Lee, Walter Tsong; Foo, Fung Joon (Journal of Surgical Specialties and Rural Practice, 2025)
Abstract The findings of the Lancet Commission have brought to light the diminished state of surgical care in low- and middle-income countries, especially the availability of surgical care in rural areas. Rural surgeons require different skillsets, and traditional surgical training is geared toward urban hospital practice. Little is known of the current state of educational support and training for rural surgery. The present study sought to investigate the state of training for surgery in austere environments by performing a review of the literature on existing courses and evaluations of their successes. The study aims to assess if there is a need for more formal resources to provide austere or rural environment surgical training. A literature search was performed on existing courses and training programs for surgery in austere environments. Courses or fellowships that imparted surgical skill for practice in rural/austere environments were included; programs that were not skill based, had no formal educational component, were nonsurgical or nonrural/austere environment related were excluded. Sixteen articles were included in the analysis. Eight pertained to short courses and eight pertained to long courses. Evaluation of outcome was performed through a mixture of knowledge assessment, competency assessment, as well as participant's assessment of usefulness. There remains a paucity of reported courses or programs focused on providing surgical education in low-resource settings. Existing interventions are largely inadequately evaluated, with a lack of focus on real-world impact. Future interventions should focus on being collaborative and systems based with longitudinal real-world evaluation to assess for meaningful impact toward achieving the 2030 Lancet Commission goals.